The Integration of AI and Metaverse in Education: A Systematic Literature Review - Khalid Almeman; Faycel EL Ayeb; Mouhebeddine Berrima; Brahim Issaoui; Hamdy Morsy (Applied Sciences)
The use of the metaverse in educational environments has grown significantly in recent years, particularly following the shift of major tech companies towards virtual worlds and immersive technologies. Virtual reality and augmented reality technologies are employed to construct immersive learning environments. The metaverse is generally understood as a vast digital ecosystem or virtual space, facilitating the transition of individuals from physical to virtual environments, and is applicable to educational domains where practical experiments are challenging or fraught with risks, such as space exploration, chemical experimentation, and flight simulation training. In addition, the integration of artificial intelligence with the metaverse within educational contexts has significantly enriched the learning environment, giving rise to AI-driven teaching systems tailored to each student’s individual pace and learning modalities. As a result, a number of research articles have been conducted to explore the applications of the metaverse and artificial intelligence in education. This paper provides a systematic literature review following the PRISMA methodology to analyze and investigate the significance and impact of the metaverse in education, with a specific focus on the integration of AI with the metaverse. We address inquiries regarding the applications, challenges, academic disciplines, and effects of integrating AI and the metaverse in education that have not yet been explored in most research articles. Additionally, we study the AI techniques used in the metaverse in education and their roles. The review affirms that the integration of the metaverse in education, with the utilization of AI applications, will enrich education by improving students’ understanding and comprehension across diverse academic disciplines.